Strategi Sosialisasi Penyuluh Agama Islam Dalam Pencegahan Perceraian - Dinda Rizky Amalia; Wahyu Ziaulhaq (Jurnal Sosial, Politik dan Budaya (SOSPOLBUD), 2022)
This study aims to describe the socialization strategy of Islamic religious educators in preventing divorce. The main purpose of this study is to educate the reader that divorce has a negative impact, namely, the splitting of love between two hearts, the child will experience mental stress disorders, the assets obtained together from the marriage will be disputed. This research is a qualitative research with a descriptive approach. Data collection techniques used are observation and structured interviews. The results of this study are: First, Islamic religious instructors provide information to the community in order to avoid themselves from household conflicts that trigger divorce. Second, provide education to the public regarding the rights and obligations of husband and wife. Third, providing opportunities for the community to consult regarding household problems. Fourth, provide advocacy to the community on the procedure for referral. The implementation of socialization carried out by Islamic religious instructors by means of lectures, discussions and questions and answers with a humanist approach.